Optimalisasi Lateks Tetesan Lanjut Menggunakan Berbagai Koagulan Anjuran - Afrizal Vachlepi (Widyariset, 2020)
Natural rubber latex will coagulate naturally about 4-6 hours after tapping. This coagulation will produce low quality rubber and inconsistent. In addition, latex will be easily lost by rain because long coagulation time, especially continuous latex droplet. The use of coagulant in the continuous latex droplet can reduce yield losses and improve quality. The purposes were to identify and study the effect of coagulants on the dry rubber content and technical quality of the rubber from continuous latex droplet of clone BPM 24. The treatments was type of coagulants consist of formic acid, pure liquid smoke, liquid smoke DS, liquid smoke DK and control (auto coagulation). Each treatment use 10 rubber tree of clone BPM 24. The parameters consists of dry rubber content, initial plasticity (Po), plasticity retention index (PRI), Mooney viscosity, viscosity stability index (SVI), volatile matter content and ash content. The quality will be analyzed statistically using the completely randomized design non factorial and will be compared with Indonesian National Standard 06-1903-2000 about Standard Indonesian Rubber (SIR). The results showed that the use of coagulant to continuous latex droplet had significant effect on PRI and Mooney viscosity of rubber. The best treatment was obtained liquid smoke DS which produce rubber with quality standards for Po 36, PRI 80.8, Mooney viscosity 68, SVI 4, ash content 0.27% and volatile matter content 0.48%. The coagulated natural rubber with liquid smoke DS can produce rubber with quality specifications SIR 20 grade CV 70.